Validação da escala de clima de equipe para o contexto hospitalar no Brasil - Ribeiro, Milena Balthazar de Souza (2019)
The climate of teamwork is a short importance subject that has been studied in recent years due to its relation with impact factors in the quality of care, in the satisfaction of professionals and patient safety. In the hospital concept, care teams are guiding resources of the assistance from a safe operation, conjunct, parallel and with quality. Owing to strengthening of these teams the present study aims to: Perform validation of the instrument Team Climate Scale (TCS) in the hospital context. Method: It is a methodological study with quantitative approach to validation of the instrument TCS with teams from a large hospital in the São Paulo interior. The scale measures the climate of teamwork based on four factors for innovation: shared vision and objective, participatory safety, innovation support and task orientation. This instrument has as its purpose describes the teamwork climate profile, characterizing their frailties and potentialities. Results: The sample was composed by 354 professionals allocated in 45 teams of permanent contact or sub permanent. Nursing assistant and technician represent 32 %. Nurses 19 % and administrative assistants 15 %. The exploratory and confirmatory factorial analyzes revealed a satisfactory adjustment for the structural model of 4 factors (CFI = 0,97; RMSEA = 0,07; SRMR = 0,03). Composite reliability indicators and Cronbach's alpha reinforce the accuracy of these factors. Scores of the teams were calculated and related to the measures of the for factors being indicated the most favored and disadvantaged factors. Favorable climates are related with multi professional teams, less complexity sectors, working day and work shift reduced. Conclusion: It was demonstrated evidence of validity based in the internal structures, discriminant validity and precision to use (TCS) together the teams in the hospital context. This scale turned out an effective instrument to diagnosis of the climate of teamwork with solid data to use in the hospital context in order to measure the climate relative to the four factors to innovation.